Biomechanical evaluation of postural stance stability / Ku Pei Xuan - Ku , Pei Xuan (2016)

(untitled)
Postural balance, which refers to the essential ability of maintaining daily functions and sports activities, is one of the major concerns in society. As the static stance control serves as the indicator of dynamic control via assessment of postural sway, it is important to identify changes among different targeted groups. Therefore, the aims of this dissertation were to assess the changes of postural stance balance among young adults, middle-aged adults and transtibial amputees. Additionally, the aim was to examine the changes of muscular response to platform stiffness. The changes of postural control among young adults according to their body mass index classification and gender during bipedic stance and unipedic stance were investigated. The findings showed that obesity may lead to a poor postural control among young adults (p < 0.001). There is a tendency for females to have better postural performance than male. Then, postural control in bipedic stance and stance with toe-extension for young adults was examined. The findings demonstrated that the center of pressure displacement of stance posture with voluntary toe-extension does not differ with bipedic stance and no gender effect towards stance control was found. In addition, the changes of postural control and electromyography response on the support surface perturbation among healthy middle-aged adult and transtibial amputee were investigated. There is also no gender effect with human balance control found for both middle-aged adult and transtibial amputee. Both groups revealed a lower relative stability for direction control as the support surface perturbation inclined. There is left-right asymmetry of lower limb muscle response and displacement of center of pressure. Furthermore, the relationship of the anthropometric variable with postural control among transtibial amputee and age-matched able-bodied group were evaluated. The relative stability of transtibial amputee was negatively correlated with increased body mass index in static stance. No relationship was found in relative stability-body mass index and relative stability-body fat percentage in dynamic stance. A strong correlation between body weight two-point discrimination sensitivity test on trans-metatarsal (r = –0.787) and mid-foot (r = –0.784). The body mass index has a strong correlation with two-point discrimination sensitivity test on trans-metatarsal (r = –0.752) and mid-foot (r = –0.826). None of the variables such as age, weight, height, Q-angle, body mass index, skinfold measurement and foot sensations were found to be a predictor for postural control among TTA. The findings have eliminated the related variables as possible balance-related factors for transtibial amputees for future research. The findings could contribute to the understanding of the possibility of anthropometric variable impact on postural stability and development new rehabilitation program for transtibial amputee.